Predicted no-effect concentrations determination and ecological risk assessment for benzophenone-type UV filters in aquatic environment. (January 2020) - Guo, Qiaorong; Wei, Dongbin; Zhao, Huimin; Du, Yuguo
Abstract: Benzophenones (BPs), a group of widely used ultraviolet filters, have been frequently detected out in multiple environment matrices even in organism bodies. Although a variety of toxicological effects of BPs have been disclosed recently, it is barely to evaluate the potential ecological risk of BPs due to lack of reference criteria. Therefore, the determination of predicted no-effect concentration (PNEC) values is necessary for assessing ecological risk of BPs and for protecting safety of aquatic organisms. The toxicological data of 14 BPs from both in vivo tests on aquatic organisms and in vitro tests on strains/cell lines were collected from previous reports, and two methods including assessment factor (AF) and species sensitivity distribution (SSD) were applied to calculate PNECs, respectively. Four groups of PNECs were obtained and compared, a final PNEC value was recommended for each BP based on reliable and conservative consideration. With these PNECs values, the risk quotients of 8 BPs from 35 ambient freshwater samples were calculated, the results demonstrated that 3 BPs including 2, 2′, 4, 4′-tetrahydroxyl-BP, 2-hydroxyl-4-methoxyl- BP, and 2-hydroxyl-4-methoxyl-5-sulfonic acid-BP exhibited high ecological risk, and the ecological risk posed by BPs in River Tiff in UK was great. It is anticipated that these results would provide useful reference for assessing and managing BP-type compounds, and for selecting toxicity data and methods to derive PNECs for emerging contaminants. Graphical abstract: Image 1 Highlights: In vivo and in vitro toxicity data were used to derive PNECs simultaneously. PNECs derived by SSD method were more reliable than those by AF method. PNECs for BPs containing 4-hydroxyl group were lower. BP10, BP11, and BP13 in ambient waters caused high ecological risk. Abstract : The predicted no-effect concentrations of 14 BPs were derived, and 3 of these BPs caused significant ecological risk in ambient freshwater.